Comparison of platforms used in online education - Papp Gabriella; Пап Габріелла (ФОП Жукова Ірина Віталіївна, 2023)
Abstract. In spring 2020, at the beginning of the pandemic, the organisation of education changed overnight. At that time, teachers were planned a short-term solution, but still looking for a reliable platform to connect with their students and deliver quality education. As time passed, they experimented with the platforms that seemed best suited to them and their students, with their advantages and disadvantages. Then, in February of last year, the difficulties encountered forced everyone back to teaching online. The experience of the past has led everyone to return to online education more routinely. In the research for this study, we looked at platforms that we have tried ourselves. We were looking for those that allowed work with the students not only in the online space but also in the creation and sharing of e-tests. Our aim was to select and test four platforms (Google Classroom, Microsoft Teams, OnlineTestPad and EduBase) for the organization of lessons and to compare them. In this paper, we present and compare these platforms on the basis of the aspects we consider important from an educational point of view. As the most prominent aspects, we have examined the ease of use of the interfaces found, such as registration and group creation. From an educational point of view, the possibilities of video calling and group and individual messaging were considered important. We also looked at the setup features, the editing of e-tests, and the online and offline distribution options. We highlight the advantages and disadvantages of the platforms. Another aim of the study was to use the comparison to help trainers find the most appropriate tool for organising online teaching and learning. We show the way towards a platform that will make it easier for the instructor to keep in touch with his students, and that will save time in measuring students' knowledge by making it easier to edit and distribute e-tests.

Резюме. Навесні 2020 року, на початку пандемії, організація освіти змінилася за одну ніч. На той час вчителі планували короткострокове рішення, але все ще шукали надійну платформу для зв'язку зі своїми учнями та надання якісної освіти. З часом вони експериментували з платформами, які, на їхню думку, найкраще підходили їм та їхнім учням, з їхніми перевагами та недоліками. У лютому минулого року, труднощі, з якими вони зіткнулися, змусили всіх повернутися до викладання онлайн. Попередній досвід показав, що варто вчителям повернутися до рутинного онлайн нфвчання. При підготовці цього дослідження ми звернули увагу на платформи, які випробували самі. Ми шукали ті, які дозволяли працювати зі студентами не лише в онлайн-просторі, а й створювати та надсилати електронні тести. Нашою метою було обрати та протестувати чотири платформи (Google Classroom, Microsoft Teams, OnlineTestPad та EduBase) для організації уроків та порівняти їх. У цій статті ми представляємо і порівнюємо ці платформи на основі аспектів, які ми вважаємо важливими з освітньої точки зору. В якості найбільш важливих аспектів ми розглянули простоту використання знайдених інтерфейсів, таких як реєстрація та створення груп. З освітньої точки зору, важливими були можливості відеодзвінків, групових та індивідуальних повідомлень. Ми також розглянули функції налаштування, редагування електронних тестів, а також варіанти надсилати їх онлайн і офлайн форм. Ми виділили переваги та недоліки платформ. Ще одна мета дослідження - за допомогою порівняння допомогти тренерам знайти найбільш підходящий інструмент для організації онлайн-викладання та навчання. Ми показуємо шлях до платформи, яка полегшить викладачеві підтримку зв'язку зі своїми студентами, а також заощадить час на вимірювання знань студентів завдяки спрощенню редагування та розповсюдження електронних тестів.
Порівняння платформ, що використовуються в онлайн-освіті
http://perspectives.pp.ua/index.php/sn/issue/view/189
Keywords: organization of education; online platforms; e-test; організація навчання; онлайн-платформи; електронне тестування